Fine mapping and identification of CaTTG1, a candidate gene that regulates the hypocotyl anthocyanin accumulation in Capsicum annuum - Jin Wang; Yao Dai; Luzhao Pan; Ying Chen; Li Dai; Yanqing Ma; Xiaoxun Zhou; Wu Miao; Muhammad Rizwan Hamid; Xuexiao Zou; Feng Liu; Cheng Xiong (Horticultural Plant Journal)
Pepper (Capsicum annuum L.) is a typical self-pollinating crop with obvious heterosis in hybrids. Consequently, the use of morphological markers during the pepper seedling stage is crucial for pepper breeding. The color of hypocotyl is widely used as a phenotypic marker in crossing studies of pepper. Pepper accessions generally have purple hypocotyls, which are mainly due to the anthocyanin accumulation in seedlings, and green hypocotyls are rarely observed in pepper. Here we reported the characterization of a green hypocotyl mutant of pepper, Cha1, which was identified from a pepper ethyl methanesulfonate (EMS) mutant library. Fine mapping revealed that the causal gene, CaTTG1, belonging to the WD40 repeat family, controlled the green hypocotyl phenotype of the mutant. Virus-induced gene silencing (VIGS) confirmed that CaTTG1 regulated anthocyanin accumulation. RNA-seq data showed that expression of structural genes CaDFR, CaANS, and CaUF3GT in the anthocyanin biosynthetic pathway was significantly decreased in Cha1 compared to the wild type. Yeast two-hybrid (Y2H) experiments also confirmed that CaTTG1 activated the synthesis of anthocyanin structural genes by forming a MBW complex with CaAN1 and CaGL3. In summary, this study provided a green hypocotyl mutant of pepper, and the Kompetitive Allele Specific PCR (KASP) marker developed based on the mutation site of the underlying gene would be helpful for pepper breeding.